Conciencia fonológica y comprensión lectora en estudiantes de segundo grado de primaria de Carmen de La Legua - Callao - Cieza Manzanares de Ortiz, Mercedes Teresa (2010)
I investigated the correlation between phonological awareness and reading comprehension in students of second grade Educational Institution of Carmen de la Lengua - Callao. It also describes the performance in phonological awareness and reading comprehension of students in the sample, the same that was with 40 students, 25 boys and 15 girls aged 7-10 years of age, who were administered the test Reading Comprehension of Language Complexity Progressive Alliende, Condemarín and Milicic and Linguistic Segmentation Test Jimenez Gonzales and Ortiz. We used descriptive statistics to analyze the results of both tests, and inferential statistics to find the relationship between them. We obtained a Spearman rho coefficient of 0.782, so it was determined that the relationship between reading comprehension and phonological awareness is statistically significant at a significance level of 0.00. This also makes a detailed analysis of the dimensions of the tests applied.